Application of Expert System for Diagnosing Diseases Cocoa Plants Using the Forward Chaining Algorithm Method - Pahlevi, Omar; Atmojo, Muhamad Kusumo (Politeknik Ganesha Medan, 2020)
Cacao plants originated from South America, then spread to North America, Africa and Asia. In Indonesia, cocoa has been known since 1560, but has become an important commodity since 1951. Cacao commodity plays an important role in the national economy and is a national mainstay commodity. This shows that cocoa is one of the results of plantation commodities that have a high economic value and play an important role as a source of foreign exchange through exports, as well as encouraging the regional economy, especially in rural areas. But behind the high value of cocoa production, there are problems faced, including the low quality of cocoa in Indonesia because cocoa plantations in Indonesia are threatened by pests and plant diseases. Lack of information that is known by the plantation and cocoa farmers about the types of diseases that attack cocoa plants, causing many cocoa plants that are not handled properly. If this is allowed to continue it will impact on the declining quality and production of cocoa plants. Current advances in information technology, especially cellular phones, can be used as a means to improve public services, one of the results of the development of cellular technology is the birth of cellular phones with the android operating system. In this research produced if the symptoms data entered could not find the type of cocoa plant disease because the input data did not match any disease data in the database, the system would display the word